Knowledge, attitude, and practice toward herpes zoster (HZ) and HZ vaccination: Concept elicitation findings from a multi-country study in the Asia Pacific - Jing Chen; Sumitra Shantakumar; Jennifer Si; Regina Gowindah; Raunak Parikh; Felix Chan; Macy Chan; Won Suk Choi; Erick Huang; Kuo-Chin Huang; Li-Min Huang; Hyungwoo Kim; et al. (Taylor & Francis Group, 2024)
ABSTRACTHerpes zoster (HZ) is a prevalent disease characterized by a painful rash. A multi‑country study was conducted to elicit public and physician knowledge, attitude, and practice (KAP) toward HZ disease and vaccination for the assessment of local factors influencing HZ vaccine perceptions in four Asian-Pacific countries/territories One-to-one qualitative interviews were conducted in 2022, among the public (people aged ≥ 50 years, adults with parents aged ≥ 50 years, zoster vaccine live-vaccinated individuals aged ≥ 50 years in Republic of Korea, and HZ patients; n = 78) and physicians (general practitioners and specialists; n = 24). Themes surrounding KAP toward HZ and HZ vaccination were summarized using a thematic analysis. A substantial knowledge gap related to HZ was observed among the public, including its causes, long-term impacts, and the at-risk population. There was a low perceived risk of HZ and low general awareness of HZ vaccine availability, although country/territory-specific differences existed. Fear of HZ-associated pain contributed toward vaccination intent among HZ patients and adults with parents aged ≥ 50 years. HZ-naïve adults who were encouraged to receive the vaccine by others were not motivated to do so due to optimism bias. Physicians were perceived to be a reliable source of information. However, physicians did not always proactively discuss HZ vaccination due to time constraints and a perceived need to prioritize other vaccinations including influenza and pneumococcal vaccines. Initiatives are needed to improve public awareness of HZ and its complications, in terms of overall impact on individuals and society, and highlight the important role of physicians in recommending vaccination.